Penyuluhan Pentingnya Penggunaan Sabun Cuci Tangan kepada Kader pada Era New Normal di Kelurahan Karikil Tasikmalaya - Meri Meri; Rudy Hidana; Dichy Nuryadin Zain; Teti Agustin; Candra Bayu (CERED Indonesia Publishing, 2021)
The Covid 19 pandemic is still ongoing for a long time, since it was established in March 2020. Efforts to break the chain of Covid-19 transmission are a shared responsibility. One of the efforts to prevent transmission is to get used to washing hands with soap. The novelty of this dedication is the lack of knowledge about the importance of using hand washing soap compared to handsanitizers in the new normal era. The target of the counseling is cadres in Karikil Mangkubumi Village, Tasikmalaya. The purpose of this service is to increase cadres' knowledge of the importance of using hand washing soap compared to handsanitzers in the new normal era. The method used is lectures and discussions about the material presented. The process of implementing outreach is carried out by stages of preparation, implementation and evaluation. Evaluation is done by giving pre-test and post-test questionnaires to the extension cadres. The results of counseling are with good criteria of 92.3% before extension to 100% after counseling. While the Sufficient criterion is 7.5% before extension to 0% after counseling. The conclusion is that all participants or cadres of extension have a level of knowledge that increases well after extension.